Vegetation composition and carbon stocks in West Batang Toru Forest Block, North Sumatra - PASARIBU, NURSAHARA; RANGKUTI, LATIFAH HANNUM; SIREGAR, JULIUS PAOLO (Universitas Syiah Kuala, 2024)
West Batang Toru Forest Block, North Tapanuli Regency, North Sumatra Province is a forest that contains numerous species of tree stands and is estimated to be able to store a considerable high carbon from the atmosphere. The aim of this study was to determine the composition of vegetation and the potential for carbon stored in the forest region. This research was conducted from September 2021 to March 2022 using a purposive sampling method. Vegetation data were analyzed using the Diversity Index (H'), Uniformity Index (E) using the Shannon-Wiener equation. The carbon stock of each stand per species was estimated using the Ketterings allometric equation. The study documented a total of 64 families, belonging to 297 species with a total of 2,399 individuals. The percentage of composition of all growth rates ranged from 31%-59%. The Importance Value Index (IVI) of all growth rates ranged between 14.3 to 71.7%. The highest diversity index and evenness index at the tree level were 4.71 and 0.85. The stored carbon is 373.227 tons C/ha in West Batang Toru Forest Block, highlighting the forest region as an important green carbon sink.